OH-MY-GOD, HOW IS THIS? OR WHAT MAKES A SONG POPULAR? - Erika KULCSÁR; Henrietta SÁNDOR (Studia Universitatis Babeş-Bolyai Negotia)
Article History: Received: 23 September 2024; Reviewed: 19 December 2024; Accepted: 27 January 2025; Available online: 26 March 2025.